Metais em água, sedimento e duas espécies de peixes com diferentes níveis tróficos em um rio subtropical brasileiro - Weber, Paula Damião (2011)
In aquatic environments, heavy metals are produced from natural and anthropogenic sources and the degree of contamination in fish tissues depend on pollutant type, fish species, sampling site, trophic level and their mode of feeding. The heavy metal concentration (Al, Cd, Co, Cr, Cu, Fe, Mn, Ni, Zn and Pb) in water, sediment and liver of two fish species (Oligosarcus spp - carnivore and Chyphocarax voga - detritovore) was analyzed at two sampling sites in Sinos River, Brazil, during the four seasons. The highest heavy metals concentration was observed in the sediment, followed by water and lowest in fish. As the sediment was the major sink for pollution by metals in this river, it probably played an important role in the uptake of these metals by the detritivore species, which accumulated more metals in the liver than the carnivore species. Furthermore, potential ecological risk was low for both sampling sites, showing the low metal contamination in this area.